2012
DOI: 10.1063/1.3675845
|View full text |Cite
|
Sign up to set email alerts
|

Molecular properties via a subsystem density functional theory formulation: A common framework for electronic embedding

Abstract: In this article, we present a consistent derivation of a density functional theory (DFT) based embedding method which encompasses wave-function theory-in-DFT (WFT-in-DFT) and the DFT-based subsystem formulation of response theory (DFT-in-DFT) by Neugebauer [J. Neugebauer, J. Chem. Phys. 131, 084104 (2009)] as special cases. This formulation, which is based on the time-averaged quasi-energy formalism, makes use of the variation Lagrangian techniques to allow the use of nonvariational (in particular: coupled clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
127
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 81 publications
0
127
0
Order By: Relevance
“…In particular, WFT-in-DFT embedding utilizes the theoretical framework of DFT embedding to enable the WFT description of a given subsystem in the effective potential that is created by the remaining electronic density of the system. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] We recently introduced a simple, projection-based method for performing accurate WFT-in-DFT embedding calculations 30 that avoids the need for a numerically challenging optimized effective potential (OEP) calculation 24,25,[31][32][33][34] via the introduction of a level-shift operator. It was shown that this method enables the accurate calculation of WFT-in-DFT subsystem correlation energies, as well as many-body expansions (MBEs) of the total WFT correlation energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, WFT-in-DFT embedding utilizes the theoretical framework of DFT embedding to enable the WFT description of a given subsystem in the effective potential that is created by the remaining electronic density of the system. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] We recently introduced a simple, projection-based method for performing accurate WFT-in-DFT embedding calculations 30 that avoids the need for a numerically challenging optimized effective potential (OEP) calculation 24,25,[31][32][33][34] via the introduction of a level-shift operator. It was shown that this method enables the accurate calculation of WFT-in-DFT subsystem correlation energies, as well as many-body expansions (MBEs) of the total WFT correlation energy.…”
Section: Introductionmentioning
confidence: 99%
“…Among these are the QM/MM, [1][2][3][4][5][6] ONIOM, 7,8 fragment molecular orbital (FMO), [9][10][11][12][13][14][15] and wavefunction theory (WFT)-in-density functional theory (DFT) embedding [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] approaches, which allow for the treatment of systems that would not be practical using conventional WFT approaches. In particular, WFT-in-DFT embedding utilizes the theoretical framework of DFT embedding to enable the WFT description of a given subsystem in the effective potential that is created by the remaining electronic density of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3. Solvatochromic shifts (in eV), oscillator strengths (in atomic units), and weight of the lowest π → π * orbital transition of pNA in (H 2 O) 18 cluster, obtained using TD-EMFT with mixedbasis B3LYP-in-LDA and B3LYP-in-FCLDA embedding, and TDDFT at the B3LYP/6-31G* and LDA/STO-3G levels of theory. The solvatochromic shifts are computed relative to the gas-phase results, which are obtained using TDDFT with B3LYP/6-31G* for the bare pNA molecule.…”
Section: Computational Detailsmentioning
confidence: 99%
“…For example, linear-scaling implementations based on linear response take advantage of spatial locality of either the atomic [5][6][7] or molecular [8][9][10][11][12][13] orbitals. An alternative strategy employs subsystem embedding to describe localized excitations, including TDDFT implementations using either fragment molecular orbitals 14 or frozen-density embedding, [15][16][17][18][19][20] as well as the QM/MM approach. [21][22][23][24] While each of these methods has merits, they also have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…This type of approach has been applied successfully in describing the effect of chloride-actinyl interactions on the f-f spectra of the NpO 2+ 2 cation. 46 The WFT-in-DFT frozen density embedding (FDE) scheme is theoretically well-defined and suitable for extension to coupled subsystems 47 and can provide an enormous reduction of both computational cost and the complexity of the data that is to be analyzed. We therefore think it is of interest to use the CUO noble gas interaction as another test case for the feasibility of the approach in describing uranium coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%